Auditor industry specialization and earnings quality around the world. - Low, Kai Ling. (2008)
We examine the effects of auditor industry specialization and the legal environment on earnings quality. Our research also highlights the importance of auditor industry specialization when the legal environment differs among countries and we seek to find possible reasons why auditor industry specialization is important when such differences are present.